Determining genetic combining ability, heterotic potential and gene action for yield contributing traits and Yellow Vein Mosaic Virus (YVMV) resistance in Okra (Abelmoschus esculentus (L.) Monech.). Issue 5 (27th October 2020) - Das, Anjan; Yadav, Ramesh Kumar; Choudhary, Harshawardhan; Singh, Saurabh; Khade, Yogesh P.; Chandel, Rahul
Abstract: Breeding for resistance to biotic stress and higher yield is a continuous process. Thus, the identification of desirable parents with good combining ability and nature of gene action for the target trait is of utmost importance. Hence, in this present investigation, 10 lines and three testers of Okra were crossed in line × tester mating design to generate 30 testcross progenies and their evaluation along with parents and check in a randomized complete block design with three replications. To depict the true picture of genetic variation among the parental genotypes, molecular diversity analysis was also carried out using genomic-simple sequence repeats before crossing to ascertain that sufficient variability is present among the parents. The molecular analysis grouped the parental genotypes into four clusters (I–IV). The analysis of variance revealed that all the treatments were significant for most of the traits. The combining ability analysis suggested Pusa A-4 as the best general combiner for earliness, Pusa Bhindi-5 for high yield, and DOV-92 for fruit length, plant height, yield per plant, and coefficient of infection for Yellow Vein Mosaic Virus Disease resistance. Similarly, the specific combining ability analysis suggested that the cross combinations DOV-92 × Pusa Bhindi-5 followed by DOV-92 × Pusa A-4 and DOV-92 × Pusa Sawani exhibit high economic heterosis for yield per plant as well as for disease resistance. Finally, estimation of the degree of dominance and predictability ratio was also worked out which indicated the prevalence of non-additive gene action for most of the traits pointing towards sufficient scope for heterosis breeding in Okra.